Erratum to: Role of transcription regulatory sequence in regulation of gene expression and replication of porcine reproductive and respiratory syndrome virus - Chengbao Wang; Han Meng; Yujin Gao; Hui Gao; Kangkang Guo; Fernando Almazan; Isabel Sola; Luis Enjuanes; Yanming Zhang; Levon Abrahamyan (Veterinary Research, 2017)
After publication of the article [1], it has been brought to our attention that an acknowledgement has been omitted from the original article. The authors would like to include the following, The authors also thank Prof. En-Min Zhou (Northwest A&F University) and his laboratory for technical support.”